Characteristics of Quality Profile and Agribusiness of Robusta Coffee in Tambora Mountainside, Sumbawa - Lya Aklimawati; Yusianto .; Surip Mawardi (Indonesian Coffee and Cocoa Research Institute, 2014)
Coffee development in Indomesia by means of optimalizing local resources needs to be done for increasing national coffee production as well as for expanding domestic and international markets. These opportunities must be used to gain benefit as a strategic action for raising farmer’s prosperity. This study was aimed to observe physical quality and flavor profile of Robusta coffee from Tambora mountainside, and to identify agribusiness coffee system applied by the farmers, including problem identification at farmer’s level. This research was carried out at Pekat Subdistrict (Dompu District) and Tambora Subdistrict (Bima District), West Nusa Tenggara Province. Direct observation and in-depth interviews were conducted in this study. Data collected consisted of primary and secondary data, as well as 11 green coffee samples from farmers to be analysed its physical quality and flavor profile. The number of respondents were nine stakeholders consisted of three farmers, two farmer group leaders, one field officer, one duty officer, one trader, and one large planter official. Respondents selection were based on convenience sampling method. The results showed that physical quality of coffee bean was belonged to Grade 4—6 (fair to poor quality), while broken beans shared the highest number of physical defects. Robusta coffee from Tambora mountainside performed good taste profile, that the coffee can be promoted to be fine Robusta by improving post harvest handling. Robusta coffee farming at Tambora mountainside was characterized by monoculture cropping system, average of land ownerships about 1 ha/household, and average productivity about 900—1,000 kg green coffee/ha/year. Major problems on Robusta coffee farming at Tambora mountainside consisted of lack of coffee plant maintenance as well as limited accessibility to financing and technology. Key words: agribusiness, physical quality, flavor, Robusta coffee, Tambora mountainside